2017
DOI: 10.1091/mbc.e17-02-0106
|View full text |Cite
|
Sign up to set email alerts
|

Nck deficiency is associated with delayed breast carcinoma progression and reduced metastasis

Abstract: Nck promotes breast carcinoma progression and metastasis by directing the polarized interaction of carcinoma cells with collagen fibrils, decreasing actin turnover, and enhancing the localization and activity of MMP14 at the cell surface through modulation of the spatiotemporal activation of Cdc42 and RhoA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 105 publications
(125 reference statements)
4
14
0
Order By: Relevance
“…Podosomes are rich in MMPs that drive matrix remodeling in various cell types . In a recent study, using human breast carcinoma cell line MDA‐MB‐231 and mouse model, we demonstrated that Nck facilitates MMP14‐mediated breast carcinoma cell invasion . In our present study, RT_PCR analysis revealed high MMP14 expression in MDA‐MB‐231 cells compared with noncancerous cells MCF‐10 and HUVEC (Figure B).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Podosomes are rich in MMPs that drive matrix remodeling in various cell types . In a recent study, using human breast carcinoma cell line MDA‐MB‐231 and mouse model, we demonstrated that Nck facilitates MMP14‐mediated breast carcinoma cell invasion . In our present study, RT_PCR analysis revealed high MMP14 expression in MDA‐MB‐231 cells compared with noncancerous cells MCF‐10 and HUVEC (Figure B).…”
Section: Discussionsupporting
confidence: 67%
“…71 In a recent study, using human breast carcinoma cell line MDA-MB-231 and mouse model, we demonstrated that Nck facilitates MMP14-mediated breast carcinoma cell invasion. 12 In our present study, RT_PCR analysis revealed high MMP14 expression in MDA-MB-231 cells compared with noncancerous cells MCF-10 and HUVEC ( Figure 5B). Other metalloproteases like ADAMs play roles in mediating cell-cell and cell-matrix interactions in both normal development and pathological states such as Alzheimer's disease, arthritis, cancer, and cardiac hypertrophy.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…NCK1 is an tyrosine kinase that regulation cell adhesion and has role in breast carcinoma cell invasion and metastasis 44 . CBL over-expression results in inhibition of transforming growth factor tumor suppressor activity and breast cancer prognosis 45 .…”
Section: T-sne (T-distributed Stochastic Neighbour Embedding) T-sne mentioning
confidence: 99%